USING OF HEALTH AND RECREATIONAL TECHNOLOGIES IN THE PROCESS OF TEACHING SWIMMING TO CHILDREN OF PRIMARY SCHOOL AGE (Physical Culture and Sport: Scientific Perspective, 2025)
In Ukraine, a number of comprehensive swimming training programs have been approved as part of physical education in secondary education institutions. However, they do not take into account the great potential of modern innovative methods and health and recreational technologies used by coaches and swimming instructors around the world. It can be argued that an in-depth analysis of these methods will open up new opportunities and approaches to the practical improvement of the process of teaching swimming to primary school students. This approach will make it possible to make the learning process easy and interesting.The purpose of the article is to analyze modern innovative methods and health and recreational technologies of teaching swimming to primary school children, which can be gradually introduced into the process of physical education in secondary schools of Ukraine or in the private practice of sports and recreation clubs.The methodology of the research included the following methods: scientific and methodological sources on the research topic, specification and comparison, pedagogical observation. The scientific novelty of the study lies in the introduction of a large arsenal of means and methods of teaching swimming in classes with schoolchildren. Among them are: health and recreational classes with elements of aqua fitness and hydro aerobics, children's yoga in the aquatic environment, dance exercises, the use of various games in the classroom, teaching applied swimming and swimming in deep water using platforms and aids.Conclusions. According to the results of the study, it is recommended to introduce innovative methods in the process of teaching preschoolers to swim, which will include not only various types of motor activity, but also various equipment (e.g. rafts, platforms). It is also necessary, first of all, to take into account the material, technical and personnel capabilities of secondary education institutions where classes are planned When introducing innovative technologies in the process of teaching children to swim, it is necessary to adhere to such criteria of technological effectiveness as scientificity, systematicity, efficiency, proceduralism, and structuredness.
Keywords: health and recreation classes; technologies; schoolchildren; swimming; innovative technologies